2007
DOI: 10.1097/01.hjh.0000298996.96430.4e
|View full text |Cite
|
Sign up to set email alerts
|

Black Africans' compliance to antihypertensive treatment

Abstract: Objectives: (i) to assess the prevalence of SAS in men with MS, (ii) to study the relationship between controlled hypertension and SAS in patients with MS, (iii) to assess the reliability of the ESS to diagnose SAS in patients with MS. Abstracts A1Methods: Among 135 men hospitalized for MS, the 125 who had no history of SAS were systematically evaluated by a nocturnal polygraphy was systematically performed in the 125 men without known SAS at the admission. An excessive daytime sleepiness was assessed by the E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 0 publications
1
6
1
1
Order By: Relevance
“…Furthermore, patients who reported using herbal preparations for the treatment of hypertension were more likely to show MNA. This is consistent with most studies on hypertension from sub-Saharan Africa that have associated the use of alternative medical therapy with MNA [ 17 , 18 , 20 , 36 , 38 ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Furthermore, patients who reported using herbal preparations for the treatment of hypertension were more likely to show MNA. This is consistent with most studies on hypertension from sub-Saharan Africa that have associated the use of alternative medical therapy with MNA [ 17 , 18 , 20 , 36 , 38 ].…”
Section: Discussionsupporting
confidence: 90%
“…Studies have also documented that forgetting to take medications is an important barrier to adherence [ 17 , 23 , 38 ]. In addition, adherence is usually better with medications that require less frequent administration [ 16 , 36 38 ]. Health education specifically about antihypertensive medications including potential side-effects, and inquiry about side-effects the patient may be experiencing and use of medications that are associated with fewer side effects may lead to improvement in adherence.…”
Section: Discussionmentioning
confidence: 99%
“…In other words, the sex of the patient is a factor determining the regularity of the monthly appointments for the renewal of treatment during the first months of treatment initiation. These results are not in line with our expectations; however, they corroborate those of Konin et al (2007) in Côte d'Ivoire. This could be explained by the low level of education among women added to the occupation status of most of them as shopkeepers or housewives.…”
Section: Discussioncontrasting
confidence: 96%
“…High cost of drug or low financial status of the population is a major deterrent in drug compliance among hypertensives. 21,22 Few studies have shown that forgetfulness was an important cause for noncompliance. 23,24…”
Section: Advices Received By Hypertensives For Bp Controlmentioning
confidence: 99%